A Systematic Literature Review and Bibliometric Analysis of Green Marketing Communication and Customer Experience in Digital Banking Adoption - Iwan Adinugroho; Luh Putu Mahyuni; Ida Bagus Teddy Prianthara (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid growth of digital banking is accompanied by an increasing focus on sustainability and customer-driven innovation. Green marketing communications and customer experience are considered important in influencing perceptions and adoption, yet their relationship remains largely unexplored. This study aims to investigate the contribution of sustainable marketing communications and customer experience to digital banking adoption. The method used was a systematic literature review with a qualitative approach. Data were collected from peer-reviewed articles in Scopus between 2020 and 2025 through a keyword strategy and multi-stage filtering, resulting in 10 relevant articles. Analysis was conducted through a thematic synthesis and bibliometric mapping approach. The results show that green communications increase trust and ethical perceptions, while customer experience strengthens satisfaction, usability, and loyalty. Both interact to create a synergistic effect in accelerating adoption. Consequently, integrating sustainable communications with optimal customer experience is key to digital banking strategies in the sustainability era. Future research should expand the scope of bibliometric indicators and incorporate a longitudinal perspective to capture the evolving dynamics of adoption.